Value Incommensurability Ethics, Risk, and Decision-Making - Andersson, Henrik; Herlitz, Anders (Routledge Studies in Ethics and Moral Theory, 2022)
Incommensurability is the impossibility to determine how two options relate to each other in terms of conventional comparative relations. This book features new research on incommensurability from philosophers who have shaped the field into what it is today, including John Broome, Ruth Chang and Wlodek Rabinowicz. The book covers four aspects relating to incommensurability. In the first part, the contributors synthesize research on the competing views of how to best explain incommensurability. Part II illustrates how incommensurability can help us deal with seemingly insurmountable problems in ethical theory and population ethics. The contributors address the Repugnant Conclusion, the Mere Addition Paradox and so-called Spectrum Arguments. The chapters in Part III outline and summarize problems caused by incommensurability for decision theory. Finally, Part IV tackles topics related to risk, uncertainty and incommensurability. Value Incommensurability: Ethics, Risk, and Decision-Making will be of interest to researchers and advanced students working in ethical theory, decision theory, action theory, and philosophy of economics.